Optimal Location of Base Station in a Wireless Sensor Network Using Gravity Location Model (International Journal of Engineering and Computer Science, 2013)
Base station location has a major impact on the network’s lifetime performance for a wireless sensor network. Due to energy constraints in individual sensor nodes, extending the lifetime is an essential objective in Wireless Sensor Networks (WSNs). Energy efficiency is a critical issue in designing the sensor networks as the nodes have limited battery power. An important characteristic for wireless sensor networks is so-called network lifetime performance, which is highly dependent upon the physical topology of the network. This is because energy expenditure at a node, to transmit data from one node another not only depends on the data bit rate but also on the physical distance between the nodes. Consequently, it is important to understand the impact of location related issues on the network lifetime performance and to optimize the topology during network deployment stage. This work considers the importance of base station placement problem for a given sensor networks such that network lifetime can be maximized. Specifically, the gravity location model is considered to identify the optimal location of the new base station, increase the life time of the sensor networks has been proposed